2012
DOI: 10.1371/journal.pone.0052341
|View full text |Cite
|
Sign up to set email alerts
|

miR-22 Controls Irf8 mRNA Abundance and Murine Dendritic Cell Development

Abstract: MicroRNAs (miRNAs) have emerged as critical regulators of many cellular responses, through the action of miRNA-induced silencing complex (miRISC)- or miRNA ribonucleoprotein complex (miRNP)-mediated gene repression. Here we studied the role of miRNAs in the development of dendritic cells (DCs), an important immune cell type that is divided into conventional DC (cDC) and plasmacytoid DC (pDC) subsets. We found that miR-22 was highly expressed in mouse CD11c+ CD11b+ B220− cDCs compared to pDCs, and was induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 63 publications
0
24
1
Order By: Relevance
“…Dendritic cells are key antigen presenting cells important to activate interferon expression by T and NK cells, and MiR-22 has been implicated in normal dendritic cell development, possibly through repression of the interferon response factor 8 (IRF8). 21 Furthermore, miR-22 has also been shown to be essential for bone marrow derived-DC and lung CD11c+ APC activation to endotoxin and other stimulants in a mechanism involving inappropriate induction of HDAC4. Indeed, impaired DC activation has been shown to interfere with cross stimulation of the TH17 response in a mouse model of emphysema 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dendritic cells are key antigen presenting cells important to activate interferon expression by T and NK cells, and MiR-22 has been implicated in normal dendritic cell development, possibly through repression of the interferon response factor 8 (IRF8). 21 Furthermore, miR-22 has also been shown to be essential for bone marrow derived-DC and lung CD11c+ APC activation to endotoxin and other stimulants in a mechanism involving inappropriate induction of HDAC4. Indeed, impaired DC activation has been shown to interfere with cross stimulation of the TH17 response in a mouse model of emphysema 22 .…”
Section: Discussionmentioning
confidence: 99%
“…showed that miR-22 suppresses IRF5 and HMGB1, two factors important to activating an interferon-mediated pro-inflammatory response through NK-κB and IRF3 20 . MiR-22 overexpression enhances development of conventional dendritic cells (cDC) through suppression of the interferon response gene Irf8 , and miR-22 is required for DC activation of TH17 responses through direct inhibition of the histone deacetylase HDAC4 21, 22 . Importantly, miR-22 has also been implicated in erythroid maturation, as expression of miR-22 was found to correlate with increasingly mature states of erythroid maturation in ex vivo culture of human CD34 + and K562 cells 23 .…”
Section: Introductionmentioning
confidence: 99%
“…miR-22 is induced in progenitor cultures by GM-CSF and it targets Irf8 mRNA for post-transcriptional repression 235 . Overexpression of miR-22 during DC development promotes the expansion of CD11b + cDC populations at the expense of pDCs.…”
Section: Development Of Pdcsmentioning
confidence: 99%
“…miRNAs post-transcriptionally control gene expression by targeting mRNAs for degradation or translational repression, and have multiple roles in various biological processes and diseases. Several miRNAs are found to be involved in the regulation of DC maturation and differentiation, such as miR-155 [105,106], miR-27 [107], miR-148/ 152a [108], miR-22 [109], miR-146a [110], etc. Recently, we established comprehensive miRNomes analysis in bone marrow HSCs, bone marrow-derived immature DCs, mature DCs and especially in the IL-10/NO-producing regulatory DCs.…”
Section: Epigenetic Control Of DC Tolerancementioning
confidence: 99%